2019
DOI: 10.1097/spc.0000000000000421
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of mucositis: critical tools for advancing pathobiological understanding and identifying therapeutic targets

Abstract: Purpose of review: Mucositis remains a prevalent, yet poorly managed side effect of anticancer therapies. Mucositis affecting both the oral cavity and gastrointestinal tract predispose to infection and require extensive supportive management, contributing to the growing economic burden associated with cancer care. Animal models remain a critical aspect of mucositis research, providing novel insights into its pathogenesis and revealing therapeutic targets. The current review aims to provide a comprehensive over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 165 publications
0
19
0
Order By: Relevance
“…Despite decades of experimental and clinical investigations of CIM, no effective therapeutic interventions are available today for treating it ( Ribeiro et al, 2016 ; Wardill et al, 2019 ). What treatments that do exist aim at reducing secondary complications to treatment, such as pain and diarrhoea.…”
Section: Possible Treatment Options For Cimmentioning
confidence: 99%
“…Despite decades of experimental and clinical investigations of CIM, no effective therapeutic interventions are available today for treating it ( Ribeiro et al, 2016 ; Wardill et al, 2019 ). What treatments that do exist aim at reducing secondary complications to treatment, such as pain and diarrhoea.…”
Section: Possible Treatment Options For Cimmentioning
confidence: 99%
“…However, these models are mostly outdated, do not report key toxicity outcome measures and lack synergy with the clinical dynamics of HDM transplantation. As such, there is a clear disconnect between the clinical understanding of HDM-induced gut toxicity and our ability to identify targetable mechanisms in a preclinical setting, hindering efforts to develop interventions that successfully translate to the clinic [24]. The current study therefore aimed to develop and characterize a new preclinical model of HDM-induced gut toxicity and identify candidate pathways for therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Its main cytotoxic effect is due to cross-linking of nucleic acid strands and inhibition of protein synthesis (Iqubal et al, 2018). In animals, cyclophosphamide (50-400 mg/kg) induces changes similar to those described for 5-FU, such as diarrhea and dyskinesia (Wardill et al, 2019). Some studies also observed this chemotherapy leads to increased intestinal permeability (Xiang et al, 2010) and epithelial destruction, in addition to dysfunction of the intestinal immunity (Owari et al, 2012).…”
Section: Animal Models Of Intestinal Mucositismentioning
confidence: 89%
“…The different treatment schemes, including dosing schedules, routes of administration, duration of treatments, and period of experimental follow-up, generally reflect the five-phase model of intestinal mucositis: initiation, messenger signaling, signal amplification, ulceration with inflammation, and healing (Sonis et al, 2004;Sougiannis et al, 2021). The main drugs used in rodent models of intestinal mucositis include 5fluorouracil (5-FU) and irinotecan; however, cyclophosphamide, cisplatin, and etoposide are also used (Ribeiro et al, 2016;Wardill et al, 2019).…”
Section: Animal Models Of Intestinal Mucositismentioning
confidence: 99%
See 1 more Smart Citation